Costs and Trade-Offs in the Fight Against the COVID-19 Pandemic : A Developing Country Perspective - Loayza, Norman V. (World Bank, Washington, DC, 2020)
The world is experiencing the worst pandemic crisis in one hundred years. By mid-April 2020, more than 80 percent of countries around the world had imposed strict containment and mitigation measures to control the spread of the disease. The economic fallout has been immense, with dire consequences for poverty and welfare, particularly in developing countries. This Brief first documents the global economic contraction and its potential impact on developing countries regarding macroeconomic performance, poverty rates, and incomes of the poor and vulnerable. It then argues that the pandemic crisis may hurt low- and middle-income countries disproportionately because most of them lack the resources and capacity to deal with a systemic shock of this nature. Their large informal sectors, limited fiscal space, and poor governance make developing countries particularly vulnerable to the pandemic and the measures to contain it. Next, the Brief reviews recent epidemiological and macroeconomic modelling and evidence on the costs and benefits of different mitigation and suppression strategies. It explores how these cost-benefit considerations vary across countries at different income levels. The Brief argues that, having more limited resources and capabilities but also younger populations, developing countries face different trade-offs in their fight against COVID-19 (coronavirus)than advanced countries do. For developing countries, the trade-off is not just between lives and the economy; rather, the challenge is preserving lives and avoiding crushed livelihoods. Different trade-offs call for context-specific strategies. For countries with older populations and higher incomes, more radical suppression measures may be optimal; while for poorer, younger countries, more moderate measures may be best. Having different trade-offs, however, provides no grounds for complacency for developing countries. The Brief concludes that the goal of saving lives and livelihoods is possible with economic and public health policies tailored to the reality of developing countries. Since "smart" mitigation strategies (such as shielding the vulnerable and identifying and isolating the infected) pose substantial challenges for implementation, a combination of ingenuity for adaptation, renewed effort by national authorities, and support of the international community is needed. The lockdowns may be easing, but the fight against the pandemic has not been won yet. People and economies will remain vulnerable until a vaccine or treatment are developed. The challenge in the next few months will be to revive the economy while mitigating new waves of infection.